Evaluation of current indirect methods for measuring LDL-cholesterol - Drobnik, Sophia; Scharnagl, Hubert; Samani, Nilesh J.; Braund, Peter S.; Nelson, Christopher P.; Hollstein, Tim; Kassner, Ursula; Dressel, Alexander; Drobnik, Wolfgang; März, Winfried (Clinical chemistry and laboratory medicine, 2025)
Objectives Accurately quantifying low-density lipoprotein cholesterol (LDL-C) is crucial for precise cardiovascular disease risk assessment and treatment decisions. The commonly used Friedewald equation (LDL-C FW ) has faced criticism for its tendency to underestimate LDL-C, particularly at high triglycerides (TG) or low LDL-C, potentially leading to undertreatment. Newer equations, such as those by Martin and Hopkins (LDL-C MH ) or Sampson (LDL-C SN ), have been proposed as alternatives. Our study aimed to assess the validity of LDL-C FW , LDL-C MH , and LDL-C SN compared to ß-quantification (LDL-C UC ), the reference method recommended by the Lipid Research Clinics. Methods Using data from three studies comprising 5,738 datasets, LDL-C was determined with the four methods in samples with TG up to 5.65mmol/L. We calculated median and mean differences, correlations, and used the Passing and Bablok regression for comparisons. Concordance/discordance analyses were conducted. Results All equations provided generally accurate LDL-C estimations with slight differences among them. At TG<1.69mmol/L, no clinically significant divergences were observed. As TG values increased, LDL-C FW offered the most accurate estimation, followed by LDL-C SN , while LDL-C MH exhibited increasingly strong positive bias. LDL-C FW was not inferior to LDL-C SN and LDL-C MH in terms of concordance/discordance. Conclusions LDL-C FW generally provided reliable estimates of LDL-C in most samples, showing non-inferiority to LDL-C SN or LDL-C MH , thereby confirming its legitimacy for routine use. Since current treatment recommendations are based on studies employing LDL-C FW , its replacement by alternatives is not justified.